Molecular variability of Macrophomina phaseolina isolates using SSR marker - PRIYANKA, PRIYANKA; MATHUR, A C; SHARMA, RIDHI SHANKAR; BAGRI, R K; MEENA, A K (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted at RARI, Durgapura, SKNAU, Jobner during kharif 2020 to analyze the genetic diversity of the 12 Macrophomina phaseolina isolates by using simple sequence repeat (SSR) markers. The SSR primers were tested for amplification of genomic DNA of Macrophomia phaseolina isolates. Total five primers of MB series were screened against twelve Macrophomia phaseolina isolates. All primes amplified scorable banding pattern. Level of polymorphism for SSR analysis ranged between 60–85.7%. The similarity matrix indicated that 12 isolates exhibited 42.82–100% similarity coefficient. The SSR analysis shows high molecular variability among the isolates grouped into five major clusters A, B, C, D and E. In the similarity matrix Mp-DPR was found to have higher value of similarity coefficient (1), whereas Mp-JSM was found to have lower value if similarity coefficient (0.42).